Human-elephant relations in Peninsular Malaysia - Lim, Teckwyn (2020)
In the Malay Peninsula, people have lived alongside Asian elephants (Elephas maximus) for around 55,000 years but our expansion now endangers the species. With the aim of gaining knowledge on how to we can live together in future, I reviewed the ecology, history, and management of human-elephant relations in the Peninsula.